Обґрунтування ефективної конструкції робочих органів тістомісильних машин - Шпак, Максим Сергійович; Данилейчук, Олег Володимирович; Литовченко, Олексій Ігорович; Чепелюк, Олена Олександрівна (My University, 2019)
For effective kneading of the dough it is important to create conditions for rapid uniform mixing of the components and sufficient product circulation during the process. First of all it depends on the configuration of the working members and their operating modes. The influence of four working members types of dough kneading machines – bladed, spiral, frame and pin – on the stages course of components primary mixing and plasticization of the dough is showed in the article. The study was performed by simulation in the FlowVision licensed software. The simulation takes into account the properties of the dough as a pseudoplastic fluid, whose viscosity and the flow index n depend on the deformation rate. In order to make an informed decision on the choice of a particular working member type, it is necessary to analyze the distribution of the mixing components concentration in the first stage of the process and the movement speed of the dough in the plasticization stage. These stages of dough kneading should be considered separately, as the properties of the dough semi-finished products and the goal to be achieved differ significantly. The duration of the primary mixing stage for the spiral kneading member is 55 s, for the pin is 40 s, and the blade is 34 s. Using of the frame working member does not ensure a mixture with an uniform components distribution within 1 min. The kneading conditions at the plasticization stage should contribute to the formation of circulating vortices. The most favorable areas of their formation are those where the product velocity is the highest and the viscosity, respectively, the lowest. The lowest viscosity values of the dough (20 – 30 Pas) are observed directly near the kneading members in the area of their movement. In other parts of the volume, the dough viscosity is much higher, reaching 200 Pas and higher. On the basis of the analysis of the zones in which the formation of circulating vortices is observed, it is recommended to provide the following distances between the edges of the working members and the equipment surfaces: for frame kneading devices 85… 90 mm, spiral and pin 40… 50 mm, blades 50… 60 mm. The cross-sectional shape of the working member in which the area of product turbulence is greatest is the circle. It is most appropriate to use pins working members for kneading flour dough semi-finished products. They provide the required degree of the components mixing within 40 s of the process beginning. Due to the small resistance when dough passes around the working members of this form, it becomes possible to intensify the treatment by increasing the frequency of rotation. This, in turn, increases the performance of the kneading equipment. It should be ensured that the dough does not overheat and if necessary make appropriate changes to the equipment design. Для ефективного замішування тіста важливо створити умови для швидкого рівномірного змішування компонентів і достатньої циркуляції продукту під час процесу. Насамперед це залежить від конфігурації робочих органів і режимів їх роботи. В статті наведені результати досліджень впливу чотирьох видів робочих органів тістомісильних машин – лопатевого, спірального, рамного і штифтового – на перебіг стадій первинного змішування компонентів і пластифікації тіста. Дослідження виконано методом імітаційного моделювання в ліцензійному програмному комплексі FlowVision. При моделюванні враховано властивості тіста як псевдопластичної рідини, в’язкість  та індекс течії n якої залежать від швидкості деформації. Щоб прийняти обґрунтоване рішення щодо вибору конкретного виду робочих органів потрібно проаналізувати розподіл концентрації компонентів, які змішуються, на першій стадії процесу та швидкість руху тістової маси на стадії пластифікації. Ці стадії замішування тіста доцільно розглядати окремо, оскільки суттєво відрізняються властивості тістових напівфабрикатів та мета, яку потрібно досягти. Тривалість етапу первинного змішування для спірального місильного органу становить 55 с, для штифтового – 40 с, лопатевого – 34 с. Використання рамного робочого органу не забезпечує отримання суміші з рівномірним розподілом компонентів протягом 1 хв. Умови замішування на стадії пластифікації мають сприяти утворенню циркуляційних вихорів. Найбільш сприятливими зонами їх формування є такі, де швидкість продукту найбільша, а в’язкість, відповідно, мінімальна. Найменші значення в’язкості тіста (20–30 Па•с) спостерігаються безпосередньо поблизу місильних органів, в області їх руху. В інших частинах об’єму в’язкість тіста значно більша, досягає 200 Па•с та вище. На основі аналізу зон, в яких спостерігається утворення циркуляційних вихорів, рекомендовано забезпечувати такі відстані між кромками робочих органів і поверхнями обладнання: для рамних перемішуючих пристроїв 85…90 мм, спіральних і штифтових 40…50 мм, лопатевих 50…60 мм. Форма поперечного перерізу робочого органа, при якій область турбулізації продукту найбільша – круг. Найбільш доцільно для замішування тістових напівфабрикатів з пшеничного борошна використовувати штифтові робочі органи, які забезпечують необхідну ступінь змішування компонентів вже за 40 с від початку процесу. Завдяки невеликому опору при обтіканні тістом робочих органів такої форми стає можливим інтенсифікувати оброблення шляхом збільшення частоти обертання. Це, в свою чергу, збільшує продуктивність тістомісильного обладнання. При цьому слід простежити, щоб не відбувалося перегрівання тіста і при необхідності вносити відповідні зміни в конструкцію обладнання.
Keywords: замішування; тісто; робочий орган; рівномірність; в’язкість; швидкість; лопать; штифт; kneading; dough; working member; uniformity; viscosity; speed; blade; pin